O alinhamento entre a contabilidade gerencial e a manufatura enxuta: estudo de casos multiplos em empresas brasileiras - Fontenelle, Amanda Oliveira (2019)
Lean thinking has proposed gains by reducing waste and failure and by intensifying continuous improvement. In this context, the Lean Accounting has emerged so that the accounting information could be aligned with the new type of production system. Some tools have been created, such as the Value Stream Costing, which enables to view the costs that are directly related and add value to the product. Based on a systematic literature review, it could be verified that there is a paucity of empirical research that presents prescriptive guidelines for applying accounting tools and practices aligned with lean manufacturing. The study herein aims at assessing the level of alignment between the management accounting systems in Brazilian companies and lean manufacturing practices. A systematic literature review was conducted in order to follow up on the theme's current state of art and to establish the constructs and dimensions for alignment. In addition, two descriptive case studies were conducted, in organizations that already have a certain maturity in the terms of application of lean manufacturing, in order to extract empirical characteristics that make it possible to measure the alignment between accounting and lean manufacturing. This research will contribute to the academic environment, filling the literature gap regarding the subject, and also to the organizational context, in which companies should know the available tools and pursue to align the entire accountingfinancial system in order to facilitate management and decision-making in business.